Respuesta :

♥ Let's solve:
♥ Simplify both sides of the equation.
♥ Simplify.
♥ Subtract 2/3h from both sides.
♥ Add 44/3 to both sides
♥ Multiply both sides by 3/(-1).
♥ H=-26


❊Here is the question you've asked:
1/3
h
8/3
−1/2
=2/3h6

❊Now we shall solve this Step-By-Step!
1/3h8/3−1/2=2/3h6
1/3h+−4/43=2/3h6

❊Subtract 2/3h from both sides:
1/3h+−44/32/3h=2/3h−62/3h
−1/3h+−44/3=6

❊Add 44/3 to both sides:
−1/3h+−44/3+44/3=−6+44/3
−1/3h=26/3

❊Multiply both sides by 3/(-1):
(3/−1)*(−1/3h)=(3/−1)*(26/3)

❊Your answer is:
h=−26

❊Merry Christmas!❊
ACCESS MORE